Association Between Maternal Characteristics and the Risk of Isolated Maternal Hypothyroxinemia - Liu, Yang; Li, Guohua; Guo, Nafei; Liu, Xiaosong; Huang, Shijia; Du, Qiaoling (Frontiers in Endocrinology, 2022)
Objective We aimed to determine the association between maternal characteristics and isolated maternal hypothyroxinemia (IMH). Methods Pregnancies registered at Shanghai First Maternity and Infant Hospital between January 2014 and September 2020 were included in this cross-sectional study. IMH was defined as free thyroxine (FT4) levels below the 10th centile with TSH within the normal reference range. Multivariable logistic regression models were used to identify potential risk factors for IMH, including demographic information, anthropometric measurements and nutritional status. Results A total of 54586 singleton pregnancies were included, involving 6084 women with IMH and 48502 euthyroid women. Multivariate logistic regression analyses showed that the variables for women with ages ≥35 (adjusted OR = 1.30, 95% CI:1.20–1.40), nonlocal residence (adjusted OR = 1.16, 95% CI:1.09–1.23), multiparas (adjusted OR = 1.11, 95% CI:1.03–1.21), prepregnant overweight (adjusted OR = 1.37, 95% CI:1.27–1.49) or obesity (adjusted OR = 1.35, 95% CI:1.18–1.54), and iron deficiency (adjusted OR = 1.27, 95% CI:1.20–1.35) were independent risk factors for IMH in the overall study population, which were identical to those in the first trimester subgroup. Conclusions Maternal characteristics were associated with the onset of IMH. Maternal age, residence of origin, parity, prepregnancy body mass index (BMI) and iron status should be comprehensively considered to evaluate the risk of IMH, according to which obstetricians could determine an optimal assessment time for thyroid function.